Importance of spontaneous succession in reclamation processes = Znaczenie sukcesji spontanicznej w procesach rekultywacji - Woźniak, Gabriela; Sierka, Edyta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The wastelands are conventionally regarded as blight on the landscape with negative environmental value. There are examples from Poland as well as from Europe that post-industrial sites have been undergone natural colonisation and succession to give in some cases ecosystems of greater diversity and biological interest than ecosystems they replaced.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)